2014
DOI: 10.1016/j.canlet.2014.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Oleanolic acid and its synthetic derivatives for the prevention and therapy of cancer: Preclinical and clinical evidence

Abstract: Oleanolic acid (OA, 3β-hydroxyolean-12-en-28-oic acid) is a ubiquitous pentacyclic multifunctional triterpenoid, widely found in several dietary and medicinal plants. Natural and synthetic OA derivatives can modulate multiple signaling pathways including nuclear factor-κB, AKT, signal transducer and activator of transcription 3, mammalian target of rapamycin, caspases, intercellular adhesion molecule 1, vascular endothelial growth factor, and poly (ADP-ribose) polymerase in a variety of tumor cells. Importantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
167
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(171 citation statements)
references
References 128 publications
(175 reference statements)
1
167
0
3
Order By: Relevance
“…It also serves as an aglycone of triterpenoid saponins that is linked with sugar chains to form glycosides. Both OA and its derivatives possess several biological activities, including hepatoprotective effects, antioxidant, anti-inflammatory, antiviral and anticancer activities (2)(3)(4). Many OA derivatives have shown their chemopreventive and chemotherapeutic functions among a series of cancer types, such as acute myeloid leukemia, breast cancer and prostate cancer (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…It also serves as an aglycone of triterpenoid saponins that is linked with sugar chains to form glycosides. Both OA and its derivatives possess several biological activities, including hepatoprotective effects, antioxidant, anti-inflammatory, antiviral and anticancer activities (2)(3)(4). Many OA derivatives have shown their chemopreventive and chemotherapeutic functions among a series of cancer types, such as acute myeloid leukemia, breast cancer and prostate cancer (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…CDDO-me exerted potent anti-inflammatory and anti-cancer activities [16][17][18]. It effectively suppressed breast cancer, lung cancer, osteosarcoma, and melanoma [18]. Previous studies have shown that the anti-tumor activity of CDDO-me is largely due to NRF2 activation and NF-κB inhibition [19].…”
Section: Introductionmentioning
confidence: 99%
“…In attempts to develop synthetic triterpenoids with enhanced efficacy, bardoxolone methyl (CDDO-methyl ester; CDDO-me; RTA402) was developed based on the scaffold of oleanolic acid. CDDO-me exerted potent anti-inflammatory and anti-cancer activities [16][17][18]. It effectively suppressed breast cancer, lung cancer, osteosarcoma, and melanoma [18].…”
Section: Introductionmentioning
confidence: 99%
“…OL widely exists in plants, such as white snake tongue grass, hawthorn fruit, clove, papaya, Ligustrum lucidum and Prunella vulgaris (11). Experimental studies have demonstrated that OL has effective liver and kidney protective properties, inhibits platelet aggregation and has hypolipidemic, hypoglycemic, anti-inflammatory, anti-cancer, anti-stress, anti-ulcer and anti-microbial properties (12,13). OL is used to treat acute jaundice, chronic poisoning hepatitis, liver fibrosis and cirrhosis (12).…”
Section: Introductionmentioning
confidence: 99%